A review of published and unpublished surveys of a red-listed 'flagship species', the Western Tragopan Tragopan melanocephalus in Azad Jammu and Kashmir, Pakistan. Issue 3 (21st September 2015) - AWAN, MUHAMMAD NAEEM; BUNER, FRANCIS; KINGDON, NEVILLE
Summary: We review all available information from previously published and unpublished material including peer-reviewed papers, technical reports, field progress reports and information from local communities and hunters on the globally threatened 'flagship species' Western Tragopan Tragopan melanocephalus in the State of Azad Jammu and Kashmir (AJ&K), Pakistan. Based on these data we summarise the species' currently confirmed distribution in AJ&K, its minimum confirmed population size and highlight possible first signs of range contraction outside protected areas. We then use a simple ArcGIS habitat model to predict the species' actual distribution in AJ&K and its potential population size. Depending on the chosen criteria for habitat suitability, the estimated maximum number of Western Tragopan in AJ&K ranges between 1, 875 and 3, 760 adult individuals. Given that AJ&K represents c.30% of the global distribution of the species, the current population estimate of 5, 000 (BirdLife International2014 ) might need reconsideration. We further illustrate the importance of critical literature reviews for little-known globally threatened species such as the Western Tragopan without which red list assessments can be at risk of relying on biased data which may easily lead to incorrect conclusions.